Fostering Interreligious Harmony in Thailand: Insight from a Thai Islamic School - Ummah, Ilmi Izzatul; Ridwan, Auliya; Kesgin, Safiye (Atthulab: Islamic Religion Teaching and Learning Journal, 2024)
The purpose of this research is to explore aspects of culture and social structure, the tools used to promote coexistence, and the collaboration between the Muslim and Buddhist communities. In the context of Thailand, pluralism, or religious and cultural diversity, plays a crucial role as it can be a potential source of conflict. One form of conflict that has arisen is the tension between the Pattani Muslim community and the Buddhist population in Thailand. However, the role of Islamic education there has a significant impact on fostering interreligious harmony. Through 26 days of participatory observation at Ar-Rabity Technological College in Thailand, this research successfully revealed that Thai society holds strong nationalistic sentiments, values religious diversity, and places a high importance on social hierarchy. Furthermore, various strategies have been employed to maintain harmony in Thailand, such as multicultural education, instilling tolerance values from an early age, and organizing cross-cultural communication seminars. Through these efforts, it is hoped that a more inclusive and harmonious environment can be cultivated amidst the religious and cultural diversity present in Thailand. Tujuan penelitian ini untuk menjelajahi aspek budaya dan struktur sosial, alat-alat yang digunakan untuk mempromosikan kerukunan, serta kolaborasi antara komunitas Muslim dan Buddha. Dalam konteks Thailand, pluralitas atau keberagaman agama dan budaya memiliki peran krusial karena dapat menjadi pemicu konflik. Salah satu bentuk konflik yang muncul adalah pertentangan antara umat Muslim Pattani dan umat Buddha Thailand. Namun, peran pendidikan Islam di sana memiliki pengaruh yang signifikan dalam merawat kerukunan antaragama. Melalui partisipasi aktif selama 26 hari di Ar-Rabity Technological College Thailand, penelitian ini berhasil mengungkapkan bahwa masyarakat Thailand memiliki rasa nasionalisme yang kuat, menghargai keragaman agama, dan memperhatikan hierarki sosial yang sangat penting. Selain itu, untuk menjaga kerukunan di Thailand, berbagai strategi telah digunakan, seperti pendidikan multikultural, penanaman nilai-nilai toleransi sejak usia dini, dan penyelenggaraan seminar komunikasi lintas budaya. Melalui upaya-upaya ini, diharapkan dapat membentuk lingkungan yang lebih inklusif dan harmonis di tengah keberagaman agama dan budaya yang ada di Thailand.